FONT DESIGN OF MODERN KARAKALPAK PRESS - Perdebaeva Kumar Rauaj qizi (Bright Mind Publishing, 2025)
In this article, we will first provide an overview of the relationship between content and form. Hegel [4] was the first to express the idea of the unity and interdependence of content and form. In his opinion, a form is a manifestation of a certain content and helps to reveal that content. Form, on the other hand, helps to present the content more clearly and understandably. This idea of Hegel contradicted the views of Aristotle. According to Aristotle, the concept of content does not exist; every thought and idea can only reach a person through some form. There is no content without form. Aristotle even called the idea, one of the main categories of content, "the unity of form." In our understanding, idea, theme, and thought are known to be units of meaning. Soviet scientists supported Hegel's views on this issue for 70 years. The views of contemporary Karakalpak scholars are based on the traditions of the Soviet era and the teachings of Hegel.